1994
DOI: 10.1161/01.atv.14.3.353
|View full text |Cite
|
Sign up to set email alerts
|

PAF-acether-degrading acetylhydrolase in plasma LDL is inactivated by copper- and cell-mediated oxidation.

Abstract: In peripheral blood, native low-density lipoprotein (LDL) is a major carrier of acetylhydrolase, the enzyme that hydrolyzes the sn-2 acetate of PAF-acether, converting it to lyso PAF-acether. By controlling the level of PAF-acether, the acetylhydrolase may regulate the biologic effects of this potent inflammatory and thrombotic mediator. The biologic oxidation of LDL appears to underlie its atherogenicity. We report here that oxidative modification of LDL led to progressive loss of associated acetylhydrolase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
5

Year Published

1995
1995
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 46 publications
3
20
0
5
Order By: Relevance
“…The possibility that the above phenomenon may be attributable to any influence of plasma factors on the Lp-PLA 2 mass assay can be excluded because we obtained similar results when we measured the enzyme mass either in total plasma or in lipoprotein subfractions completely separated from the other plasma components. Another possibility could be the well-known increased susceptibility of sdLDL to oxidation (33 ) because, according to data published previously by our group and others, during lipoprotein oxidation the enzyme activity is significantly reduced (34,35 ). We found no evidence of oxidation in any lipoprotein subfraction, however.…”
Section: Discussionsupporting
confidence: 58%
“…The possibility that the above phenomenon may be attributable to any influence of plasma factors on the Lp-PLA 2 mass assay can be excluded because we obtained similar results when we measured the enzyme mass either in total plasma or in lipoprotein subfractions completely separated from the other plasma components. Another possibility could be the well-known increased susceptibility of sdLDL to oxidation (33 ) because, according to data published previously by our group and others, during lipoprotein oxidation the enzyme activity is significantly reduced (34,35 ). We found no evidence of oxidation in any lipoprotein subfraction, however.…”
Section: Discussionsupporting
confidence: 58%
“…The increase in biological activity of oxidatively modified DFP * LDL we observe may be attributable to an increase in the amount of biologically active phospholipids, due to the loss of the initial hydrolytic activity provided by LDL-associated PAF-AH. It has previously been shown that oxidation depletes LDL of PAF hydrolytic activity (24,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…(2) The lipid peroxidation products transferred from oxidized LDL may directly inactivate the PAF-AH activity in HDL 2 . Dentan and colleagues 40 have demonstrated that 4-hydroxynonenal generated during LDL oxidation may inhibit PAF-AH activity, either by a direct modification of amino acid side chains in PAF-AH or by a modification of the phospholipid environment of the enzyme at the surface of the lipoprotein particle. In conclusion, our study demonstrates that HDL 2 from subjects with poorly controlled NIDDM, in both fasting and postprandial states, exhibits decreased protection against macrophage-mediated LDL oxidation, and this may contribute to accelerated atherosclerosis in type 2 diabetes.…”
Section: Gowri Et Al Decreased Protective Function Of Hdl In Niddm 2231mentioning
confidence: 99%